2019
DOI: 10.1093/ajcn/nqy309
|View full text |Cite
|
Sign up to set email alerts
|

Grape or grain but never the twain? A randomized controlled multiarm matched-triplet crossover trial of beer and wine

Abstract: Background Alcohol-induced hangover constitutes a significant, yet understudied, global hazard and a large socio-economic burden. Old folk wisdoms such as “Beer before wine and you'll feel fine; wine before beer and you'll feel queer” exist in many languages. However, whether these concepts in fact reduce hangover severity is unclear. Objectives The aim of this study was to investigate the influence of the combination and ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
4
16
1
Order By: Relevance
“…AMEDs were the least consumed beverages ( N = 30, truex¯ = 2.87), and although wine was consumed by a similar number of people ( N = 31), on average it was consumed at a higher level (truex¯ = 7.16 drinks). Thus, our data confirm other findings using other methodology [50] showing that irrespective of the type of alcoholic drink or mixer, the most meaningful association was between the number of drinks consumed and BAC.…”
Section: Discussionsupporting
confidence: 91%
“…AMEDs were the least consumed beverages ( N = 30, truex¯ = 2.87), and although wine was consumed by a similar number of people ( N = 31), on average it was consumed at a higher level (truex¯ = 7.16 drinks). Thus, our data confirm other findings using other methodology [50] showing that irrespective of the type of alcoholic drink or mixer, the most meaningful association was between the number of drinks consumed and BAC.…”
Section: Discussionsupporting
confidence: 91%
“…AMEDs were the least consumed beverages (N = 30, = 2.87), and although wine was consumed by a similar number of people (N = 31), on average it was consumed at a higher level ( = 7.16 drinks). Thus, our data confirm other findings using other methodology [50] showing that irrespective of the type of alcoholic drink or mixer, the most meaningful association was between the number of drinks consumed and BAC.…”
Section: Discussionsupporting
confidence: 91%
“…When looking at their unique contributions to the variance explained, the strongest predictor was subjective intoxication (48.5%), followed by sleep quality (7.2%), estimated BAC (1.2%), and body mass index (BMI; 1.1%). These findings are in line with two other recent regression analyses [17,18]. Both studies showed that subjective intoxication (perceived drunkenness), and not BAC, was the strongest predictor of hangover severity.…”
supporting
confidence: 91%